Subgrade Soil Stabilization for Road Construction Using Limestone and Soil Stabilizer Additives in Arso XIV - Mesak Albertus Masoka; Petrus Bahtiar (Asian Journal of Social and Humanities, 2026)
Low subgrade bearing capacity is one of the major challenges in road construction, particularly in areas dominated by high-plasticity clay soils that are vulnerable to water saturation and structural deformation. The Arso XIV road section in Keerom Regency, Papua, experiences similar problems due to poor soil characteristics, resulting in low California Bearing Ratio (CBR) values that require stabilization treatment. This study aims to determine the physical and mechanical characteristics of the existing subgrade soil, evaluate the effect of limestone addition at various proportions, and analyze the effectiveness of Soil Stabilizer additives in improving soil bearing capacity. A quantitative experimental method was applied through laboratory testing using native soil, limestone variations of 10%, 20%, and 30%, and an additional 2% Soil Stabilizer additive. The tested parameters included Atterberg limits, specific gravity, standard Proctor compaction, and submerged California Bearing Ratio (CBR) based on applicable technical standards. The results showed that limestone and Soil Stabilizer combinations significantly improved soil properties by reducing the plasticity index, increasing maximum dry density, and enhancing CBR values. The highest performance was achieved in the mixture of 30% limestone and 2% Soil Stabilizer, which increased the CBR value from 2.20% to 7.60%, representing an improvement of approximately 245%. The study concludes that the combination of local limestone and Soil Stabilizer is an effective and sustainable alternative for improving subgrade quality and supporting road construction in Arso XIV, Keerom Regency.